2019
DOI: 10.1111/dme.14121
|View full text |Cite
|
Sign up to set email alerts
|

Loss of incretin effect contributes to postprandial hyperglycaemia in cystic fibrosis‐related diabetes

Abstract: Aim To investigate the incretin axis in people with cystic fibrosis. Methods Adults with cystic fibrosis‐related diabetes, cystic fibrosis without diabetes, and controls (adults without cystic fibrosis and without diabetes) underwent an oral glucose tolerance test and then a closely matched isoglycaemic i.v. glucose infusion. On each occasion, glucose, insulin, C‐peptide, total and active glucagon‐like peptide‐1 and gastric inhibitory polypeptide responses were recorded and incremental areas under curves were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
(34 reference statements)
0
8
0
1
Order By: Relevance
“…Experimental studies suggest that consumption of macronutrients results in acute anti-resorptive effects on bone, and that hormones involved in nutrient metabolism, such as the gut-derived incretins GIP and GLP-1, as well as insulin contribute to these effects [9] , [30] , [31] , [32] . Cystic fibrosis is associated with a unique form of diabetes that involves deranged incretin and insulin responses to macronutrient consumption [33] , [34] . Deficits in bone density and increased fracture risk are reported in patients with CF [35] , [36] ; thus, invoking disruption to the “gut-bone axis” as a plausible contributor to CF related bone disease.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies suggest that consumption of macronutrients results in acute anti-resorptive effects on bone, and that hormones involved in nutrient metabolism, such as the gut-derived incretins GIP and GLP-1, as well as insulin contribute to these effects [9] , [30] , [31] , [32] . Cystic fibrosis is associated with a unique form of diabetes that involves deranged incretin and insulin responses to macronutrient consumption [33] , [34] . Deficits in bone density and increased fracture risk are reported in patients with CF [35] , [36] ; thus, invoking disruption to the “gut-bone axis” as a plausible contributor to CF related bone disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in normal subject exposed to 6-week exercise intervention and a validation cohort ( 96 ) revealed that at baseline, eCB and paracannabinoid levels were associated with higher microbiome diversity, negatively associated with Escherichia/Shigella and Collinsella , whose increased levels are found in type 2 and gestational diabetes ( 97 ), and negatively associated with weight loss and insulin sensitivity ( 98 ). Levels of endo- and paracannabinoids were also associated with higher levels of the microbiota-produced SCFA butyrate, along with increases in the anti-inflammatory cytokine IL-10 and decreases in pro-inflammatory cytokines like IL-8 and TNFα ( 96 ).…”
Section: Intestinal Microbiota Interactions With the Endoca...mentioning
confidence: 99%
“…Тем не менее альтернативные мнения исследователей [ 32 ] и данные систематического Кокрановского обзора [ 35 ] о методах оптимальной коррекции гликемии, ввиду отсутствия убедительных доказательств преимуществ инсулинов длительного или короткого действия перед пероральными гипогликемическими препаратами в контроле клинических исходов МВСД, также заслуживают внимания. Изучаются возможности применения ингибиторов дипептидилпептидазы-4 [ 7 ], агонистов рецепторов глюкагоноподобного пептида-1 [ 36 ] для улучшения секреции инсулина, сохранения массы β-клеток.…”
Section: муковисцидоз и сахарный диабетunclassified